Nucleoside analog cytotoxicity and bystander cell killing of cancer cells expressing Drosophila melanogaster deoxyribonucleoside kinase in the nucleus or cytosol. - Zheng, X.; Johansson, M.; Karlsson, A. (Biochemical and Biophysical Research Communications, 2001)
We have recently shown that the overexpression of Drosophila melanogaster multisubstrate deoxyribonucleoside kinase (Dm-dNK) in cancer cell lines increases the cells' sensitivity to several cytotoxic nucleoside analogs and the enzyme may accordingly be used as a suicide gene in combined gene/chemotherapy treatment of cancer. To further characterize the enzyme for possible use as a suicide gene, we constructed a replication-deficient retroviral vector that expressed either the wild-type enzyme that localizes to the cell nucleus or a mutant (arg247ser) that localizes to the cytosol. A thymidine kinase-deficient osteosarcoma cell line was transduced with the recombinant virus and we compared the sensitivity and bystander cell killing when the cell lines were incubated with the pyrimidine nucleoside analogs (E)-5-(2-bromovinyl)-2'-deoxyuridine and 1-beta-D-arabinofuranosylthymine. In summary, we showed that the cells' sensitivity and the efficiency of bystander cell killing were not dependent on whether Dm-dNK was located in the nucleus or cytosol.